Thermodynamic analysis and life cycle assessment of the heating strategies in historical buildings: a case study. (28th February 2014) - Abusoglu, Aysegul; Sedeeq, Murad S.
This paper presents the thermodynamic analysis and life cycle assessment (LCA) of the heating strategies in historical buildings. We evaluated two main systems used in historical buildings to provide heat: a central heating system, which is based on a method of heating the whole air volume within the building, and a localised heating system, which is based on a method of supplying the desired amount of heat to the individual occupants. After evaluating both systems in a historic mosque, we found that using a modern localised heating system like the carbon film heating, a comfortable temperature can be maintained while saving 22.4 MWh of electricity annually, compared with a conventional central heating system. Moreover, the carbon film heating system can reduce stress on the environment by 60% when compared with the conventional heat pump system.